Eco-friendly superabsorbent composite based on sodium alginate and organo-loess with high swelling properties. Issue 66 (19th July 2015) - Ma, Guofu; Ran, Feitian; Yang, Qian; Feng, Enke; Lei, Ziqiang
<x xml:space="preserve">Abstract</x> A novel superabsorbent composite with high swelling properties was synthesized by the grafted co-polymerization of partially neutralized acrylic acid (AA) onto a sodium alginate (NaAlg) backbone in the presence of organo-loess.